PEMANFAATAN METODE DNA KRIPTOGRAFI DALAM MENINGKATKAN KEAMANAN CITRA DIGITAL - Kharisma Mahesa; Bambang Sugiantoro; Yudi Prayudi (JURNAL ILMIAH INFORMATIKA, 2019)
There are many data transmitted on internet and certainly has positive and negative side. Negative side that perceived is the increase in cybercrime activities which is a threat to everyone. Securing confidential data is very necessary so that the data is not misused by others for individual or groups benefit. This research is developing an application that is able to secure data like digital images by applying cryptography. Cryptography is the most appropriate way to secure data like digital images. DNA cryptography is one of cryptography method. Beside to application of computing is very easy, this method has excess speed in processing, use minimal storage and power usage. The result from this research are application that are built can encrypt dan decrypt digital images which has a lot color distribution well. Application and method used will work well on image that have a lot or even distribution colors. But not in digital images that have 1 dominant or transparent color in that.